Estimating HIV Disclosure and Its Impact on Social Relations: A Cross-Sectional Study in Gujarat, India - Parikh, Khushali D; Rupani, Mihir (National Journal of Community Medicine, 2024)
Background: The disclosure of HIV-positive status can significantly impact social relationships. This study aimed to evaluate the prevalence of self-disclosure of HIV status and its effects on social relations among individuals living with HIV (PLHIV) in Gujarat, India. Methods: Conducted from April to June 2021, this cross-sectional study involved 383 PLHIV attending a tertiary-care medical college hospital in Gujarat, India. The sample size was determined using Epi Info software version 7. Data collection utilized a structured questionnaire covering socio-demographic information, HIV disclosure status, and its impact on social relationships. Multiple logistic regression analysis identified predictors of non-disclosure of HIV status to spouses. Results: Among the 383 participants, 83% disclosed their HIV status to their spouse, while disclosure rates to other social contacts varied. Post-disclosure, 7% reported strained or broken relationships with their spouses. Factors associated with non-disclosure to spouses included older age (adjusted odds ratio [aOR] 1.13, 95% confidence interval [CI] 1.07-1.20), female gender (aOR 6.00, 95% CI 1.81-19.88), lack of post-test counselling (aOR 3.29, 95% CI 1.01-10.70), and spouse being HIV-negative (aOR 3.60, 95% CI 1.27-10.25). Conclusion: In conclusion, while a significant proportion of PLHIV disclosed their HIV status to spouses, a notable proportion experienced strained relationships post-disclosure. Addressing barriers to disclosure, especially among older individuals and females, and ensuring adequate post-test counselling, may facilitate open communication and support among PLHIV and their social networks.